Unveiling the causative role of promoter variant rs113823671 in MMP7 in gallbladder cancer susceptibility - Vinay Jeeyar; Kusumbati Besra; Shivaram Prasad Singh; Manjusha Dixit (Scientific Reports)
Abstract Gallbladder cancer (GBC) poses a significant global health threat, claiming 89,031 lives worldwide in 2022. This malignancy exhibits distinct genetic susceptibility patterns among populations, coupled with its aggressive nature and dismal prognosis. Among the factors implicated in cancer progression, Matrix Metalloproteinase 7 (MMP7) has emerged as a crucial biomarker due to its dual role in cancer causation and progression, but its role in GBC is completely unexplored. We hypothesized that promoter SNPs could modulate MMP7 expression, thus impacting GBC susceptibility. Our study aimed to assess the aberrant expression levels and genetic polymorphisms of MMP7 as potential risk factors for GBC. Initial screening of MMP7 promoter polymorphisms in a cohort of fifty GBC patients and controls using Sanger sequencing was followed by validation in a larger sample set comprising 300 GBC cases and 300 controls. Additionally, MMP7 protein expression was examined through immunohistochemistry in GBC tissue samples. Functional analysis of identified risk variants was carried out using luciferase reporter assays and in vitro promoter analysis in two cell lines to elucidate their impact on gene expression. MMP7 promoter variants, rs113823671 A > C (p-value = 0.034) and rs17098318 G > A (p-value = 0.024), exhibited significant associations with GBC. Reporter assays in two cell lines indicated that carriers of the risk allele ‘A’ at rs113823671 exhibited increased luciferase reporter activity, whereas no significant reporter activity was observed at rs17098318. MMP7 expression levels were markedly elevated in GBC compared to adjacent uninvolved normal tissue. Furthermore, genotype-phenotype analysis in tissue samples revealed that risk allele carriers exhibited higher MMP7 expression levels, with the correlation aligning with genetic association models. In conclusion, our study unveils the association of two novel MMP7 promoter risk variants, rs113823671, and rs17098318, with GBC and their role in GBC pathogenesis.